Marine actinomycetes Nocardiopsis alba MCCB 110 has immunomodulatory property in the tiger shrimp Penaeus monodon. Issue 102 (July 2020) - Sunish, K.S.; Biji, Mathew; Rosamma, Philip; Sudheer, N.S.; Sreedharan, K.; Mohandas, A.; Singh, I.S. Bright
Abstract: Shrimp farming constitutes an important source of revenue and employment in many developing countries. However, the shrimp industry has always been plagued with infectious diseases having varied aetiologies. Dominated by non - specific immune mechanism, preventive health care strategy is the most appropriate approach to protect the crop. The present study evaluated the efficacy of an actinomycete, Nocardiopsis alba MCCB 110 in eliciting non - specific immune mechanism in Penaeus monodon having Vibrio harveyi as the challenge organism. Haemocyte count, total protein, phenoloxidase, reactive oxygen intermediates, acid and alkaline phosphatase as well as the gene expression of proPO, peroxinectin, transglutaminase, alpha 2-macroglobulin, astakine, crustin, and penaeidin-3 were evaluated. The results demonstrated that the phenoloxidase, respiratory burst, total protein, acid and alkaline phosphatases were higher in the haemolymph of shrimps fed with Nocardiopsis alba MCCB 110 incorporated feed before and after challenge with Vibrio harveyi, compared to those of placebo fed animals. Up-regulation of six immune genes (alpha 2 macroglobulin, penaeidin −3, transglutaminase, proPO, crustin and peroxinectin) during the post-challenge were recorded. Survival of shrimp among the Nocardiopsis alba administered ones was 83% while it was 50% in placebo fed group. The elevated levels of nonspecific immune gene transcripts and concurrent increase in non specific immunity besides the higher survival rate in the Nocardiopsis alba administered group demonstrated the immunomodulatory property of the marine actinomycete Nocardiopsis alba MCCB 110 in the tiger shrimp Penaeus monodon, and on administering it through diet shrimp could be protected from vibriosis especially of V. harveyi . Highlights: A marine actinomycete Nocardiopsis alba MCCB 110 administered through diet enhanced innate immune responses such as phenol oxidase, respiratory burst, total protein, acid and alkaline phosphatases in the tiger shrimp Penaeus monodon. Nocardiopsis alba supplementation up-regulated the gene expression of alpha 2 macroglobulin, penaeidin −3, transglutaminase, proPO, crustin and peroxinectin. The survival of shrimp among Nocardiopsis alba administered ones was 83% while it was 50% in control during the post-challenge period with Vibrio harveyi. This work demonstrated the immunomodulatory property of marine actinomycete Nocardiopsis alba MCCB 110 in the tiger shrimp Penaeus monodon..